2008
DOI: 10.1111/j.1365-2222.2008.03087.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and allergic symptoms in relation to house dust endotoxin: Phase Two of the International Study on Asthma and Allergies in Childhood (ISAAC II)

Abstract: SummaryBackground Several studies have consistently reported inverse associations between exposure to endotoxin in house dust and atopy. With regard to the association between house dust endotoxin and asthma, the results are inconsistent. Objectives To study the association between house dust endotoxin levels and respiratory symptoms and atopy in populations from largely different countries. Methods Data were collected within the International Study on Asthma and Allergies in Childhood Phase Two, a multi-centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 30 publications
4
64
3
3
Order By: Relevance
“…Findings from epidemiological studies are less consistent [74]. Whereas some reports suggest a protective effect of endotoxins on the development of allergies [57,[75][76][77], others found that the exposure to endotoxins constitutes a risk factor for respiratory symptoms [78][79][80][81][82][83][84], which might depend on the amount of exposure [85].…”
Section: Endotoxinsmentioning
confidence: 80%
See 2 more Smart Citations
“…Findings from epidemiological studies are less consistent [74]. Whereas some reports suggest a protective effect of endotoxins on the development of allergies [57,[75][76][77], others found that the exposure to endotoxins constitutes a risk factor for respiratory symptoms [78][79][80][81][82][83][84], which might depend on the amount of exposure [85].…”
Section: Endotoxinsmentioning
confidence: 80%
“…However, several population-based studies have shown a decreased risk of wheezing [76], asthma [57,76] and atopy [76,88] in children living in urban homes with high endotoxin concentrations. Such a protective effect has been observed previously in rural populations, especially in the case of allergic sensitisation and atopic wheezing [75,89].…”
Section: Endotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In damp buildings, mould and bacteria grow by enjoying the hospitable environment existing in settled dust (Lim et al 2015). Endotoxin (found in the outer cell membrane of gram-negative bacteria) (Gehring et al 2008) and (1,3)-β-glucan (found in the cell-walls of mould) (Iossifova et al 2007) are the two common compounds living in building dampness, causing proinflammatory effects (Lim et al 2015). Given these explanations, it can be inferred that the level of seriousness and the period of emerging symptoms once the occupants are exposed to sick environments can be highly variable.…”
Section: Tssa (2010)mentioning
confidence: 99%
“…Ever since Strachan published the theory on the hygiene hypothesis [1], it has become more and more apparent that exposure to microbial cell wall agents (MCWAs) plays an important role in the pathogenesis of these diseases. There are numerous studies that demonstrate an influence of bacterial endotoxin (lipopolysaccharide; LPS) on atopy, allergic skin disease, and asthma [2][3][4][5][6]. Endotoxin as such causes an inflammatory response in the airways and has been shown to increase the frequency of wheeze and airways irritation among children as well as adults.…”
Section: Introductionmentioning
confidence: 99%